Imagining Others’ Minds: The Positive Relation Between Children’s Role Play and Anthropomorphism - Severson, Rachel L.; Woodard, Shailee R. (Frontiers in Psychology, 2018)
Children’s role playing, whether personifying toys or imagining invisible friends, involves imagining others’ minds and internal states. Similarly, anthropomorphism – the attribution of internal states to non-human others (e.g., animals, inanimate nature, or technologies) – also involves imagining others’ minds and internal states. We propose that the imaginative process of simulating and projecting internal states is common to both role play and anthropomorphism. The current study investigated the relation between children’s role play and anthropomorphism. Ninety children (5, 7, and 9 years) were administered Individual Differences in Anthropomorphism Questionnaire – Child Form (IDAQ-CF), comprised of the technology-inanimate nature and animal subscales, and the Role Play Scale, which assessed (a) impersonation of animals, people, and/or machines and (b) imaginary companions (ICs), including invisible friends and personified toys. Results indicated that the imaginative act of impersonating an animal, person, and/or machine was positively related to anthropomorphism, and specifically anthropomorphism of inanimate nature and technology. Second, anthropomorphism of animals was highest amongst children with invisible ICs, followed by those with toy ICs and those who impersonated. Finally, children who frequently engaged with an invisible ICs more readily anthropomorphized in general and technology and inanimate nature in particular relative to all other children. Results are discussed in terms of the differing degrees of imagination involved in anthropomorphism of animals versus technology and inanimate nature.